Dipole charge density mapping integrated in robotic ablation: first-in-human experience. (19th May 2022) - Gagyi, R; Noten, AME; Wijchers, S; Yap, SC; Bhagwandien, R; Hoogendijk, M; Szili-Torok, T
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Remote magnetic navigation (RMN) provides increased precision and catheter stability. Its atraumatic catheter design has a superior safety profile. Formerly, only the CARTO 3D mapping system was integrated in the RMN system. Recently, a novel high-resolution non-contact mapping system (AcQMap) can be used in combination with RMN robotics (AcQMap-RMN). Purpose: To assess safety, efficiency and efficacy of dipole charge density mapping in RMN guided catheter ablation (CA) procedures. Methods: All CA procedures using the AcQMap-RMN system were analyzed in 147 consecutive patients. Procedural efficiency was characterized by procedure time, total ablation time, radiation times and doses. Acute success was defined by arrhythmia source elimination. Efficacy data are based on 12-month follow up and number of redo procedures. Procedural safety was evaluated by intra- and post-procedural complications. Results: Seventy-one out of 147 patients had atrial fibrillation (AF) (24 PAF, 47 persAF). Five AF patients underwent re-isolation-only procedure, 42 patients had AcQMap based substrate ablation, and the remaining 24 patients converted to atrial tachycardia/atrial flutter (AT/AFL) during ablation. Seventy-six patients were referred for supraventricular tachycardia, including 8 patients with perinodal AT, 3 patients with inappropriate sinus tachycardia and 65 patients with AT/AFL. Thirty-eight patients were mapped with de novo, 22 with post-PVI, and 5 with post-MAZE AT/AFL. The mean procedure time was 167.6±56.5 min, mean ablation time 1228.0 (IQR 562.2-2007.2) s, mean radiation time 21.5±9.6 min, and dose was 160.0(IQR 102.0-302.0) mGy. Acute success was achieved in 137 procedures (93.1%). Twenty-three patients with PAF (95.8%), and 34 patients with persAF (72.3%) were AF-free at the end of the follow-up period. Four de novo AT/AFL patients (10.5%) and 3 post-PVI/post-MAZE AT/AFL patients (11.1%) had documented recurrence at the end of the follow-up period. Nine patients were referred for redo procedures. Minor complications were reported in 5 patients (4 groin hematomas and 1 transient ischemic attack). Conclusion: AcQMap-RMN integration provides high acute and long-term success rates, without negative impact on the safety profile. It allows mapping of a broad spectrum of arrhythmias.